PENGARUH MODEL PEMBELAJARAN BERBASIS PENGALAMAN (EXPERIENTAL LEARNING) TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMPN 3 KECAMATAN HARAU - Hendrisman Hendrisman (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to (1) empirical data on the effect of Experiental Learning Learning Model on Students 'Skill Text Writing Skills, (2) to know the empirical data on the effect of Experiental Learning Learning Models on Students' Skill Text Writing Skills. Data analysis shows that experiential learning models have an effect in learning to write description texts in the experimental class. This is evidenced by an increase in student scores after applying experiential learning learning models, obtained an increase in student learning outcomes at posttest with an average () 79.77, with the t test (t-test) prove tcount with ttable (6,7331> 2,060), because tcount is greater than ttable, Ha (alternative hypothesis) is accepted. While the conventional method also influences the learning of writing description texts of students in the control class. Evidenced by an increase in student grades, the average pretest time () 57.35. Posttest with an average () of 65.08, with the t test (t-test) proves tcount with ttable (4.3990> 2.060), because tcount is greater than ttable then Ha (alternative hypothesis) is accepted. Based on the test results that there is a significant influence between the learning outcomes of writing descriptive text between experiential learning models and conventional methods. So, the learning outcomes of experimental class students who are taught with experiential learning models are better than the learning outcomes of control class students who are taught using conventional methods